2022
DOI: 10.3390/ijms232012157
|View full text |Cite
|
Sign up to set email alerts
|

Carrot DcALFIN4 and DcALFIN7 Transcription Factors Boost Carotenoid Levels and Participate Differentially in Salt Stress Tolerance When Expressed in Arabidopsis thaliana and Actinidia deliciosa

Abstract: ALFIN-like transcription factors (ALs) are involved in several physiological processes such as seed germination, root development and abiotic stress responses in plants. In carrot (Daucus carota), the expression of DcPSY2, a gene encoding phytoene synthase required for carotenoid biosynthesis, is induced after salt and abscisic acid (ABA) treatment. Interestingly, the DcPSY2 promoter contains multiple ALFIN response elements. By in silico analysis, we identified two putative genes with the molecular characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…deliciosa is a salt-sensitive cultivar that leads to decreased vegetative growth, reduced vegetative development, and lower photosynthetic yield when exposed to saline conditions [52,53]. The development of transgenic kiwi plants with increased carotenoids and tolerance to salt stress has been proposed as a useful strategy to overcome this issue [60,61]. Of note, it has been reported that LCYB plays a key role in carotenoid biosynthesis and accumulation in kiwi [62].…”
Section: Ectopic Expression Of Dclcyb2 In a Deliciosa Increase Salt T...mentioning
confidence: 99%
See 2 more Smart Citations
“…deliciosa is a salt-sensitive cultivar that leads to decreased vegetative growth, reduced vegetative development, and lower photosynthetic yield when exposed to saline conditions [52,53]. The development of transgenic kiwi plants with increased carotenoids and tolerance to salt stress has been proposed as a useful strategy to overcome this issue [60,61]. Of note, it has been reported that LCYB plays a key role in carotenoid biosynthesis and accumulation in kiwi [62].…”
Section: Ectopic Expression Of Dclcyb2 In a Deliciosa Increase Salt T...mentioning
confidence: 99%
“…Of note, it has been reported that LCYB plays a key role in carotenoid biosynthesis and accumulation in kiwi [62]. By following the previously published transformation protocol [61], we obtained A. deliciosa-transformed calli that were subjected to chronic NaCl survival assay [62] to preliminarily evaluate the salt tolerance conferred by the ectopic expression of DcLCYB2. Two-month-old transformed calli were placed on a solid half-strength MS medium supplemented with ascending NaCl concentrations, and survival rate was determined at 5 and 15 days of chronic treatment ( Figures 4A,B and S6) by quantification of green living calli or dark dead calli.…”
Section: Ectopic Expression Of Dclcyb2 In a Deliciosa Increase Salt T...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, finding genes or molecular markers related to the traits is vital for fruit tree breeding. Modern techniques, for example, transcriptome, proteomics, and genomics can help screen salt-tolerancerelated genes or molecular markers [2,7,8]. Combining cross-breeding with transcriptome sequencing technology to screen kiwifruit salt-tolerance-related genes is helpful for assisting in the breeding of salt-tolerant varieties [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that kiwifruit, like other salt-intolerant species, exhibit slowed growth, yellowing of leaves, and even death under salt-stressed environmental conditions [11]. The study of tree transcriptomes enables us to obtain new insights into the genetic basis for the formation of tree traits [7,8,10]. The study of salt stress response in plants has become a hot topic, and transcriptomic analysis has identified metabolic pathways associated with salt stress, including plant hormone signal transduction [12], lignin synthesis [13], starch, and the sucrose metabolism pathway [14,15].…”
Section: Introductionmentioning
confidence: 99%